2010
DOI: 10.1007/s00417-010-1499-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-glue assisted multilayered amniotic membrane transplantation in surgical management of pediatric corneal limbal dermoid: a novel approach

Abstract: PurposeTo report a new surgical technique for excising pediatric corneal limbal dermoid and the post-resection ocular surface reconstruction.MethodsWe describe a method of deep lamellar excision followed by sutureless multilayered amniotic membrane transplantation in surgical management of corneal limbal dermoid.ResultThis technique achieves a rapid corneal re-epithelization, reduces post-operative pain, and will diminish post-operative scarring. Preoperative corneal astigmatism will persist.ConclusionThis met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…The poor outcome of amniotic membrane transplantation in our study stands in contrast to the previous reports. 10,12,13 All eyes treated with Mitomycin C, however, showed no development of a pseudopterygium during the follow-up. Therefore, a beneficial effect of Mitomycin C on postoperative pseudopterygium formation has to be considered likely.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The poor outcome of amniotic membrane transplantation in our study stands in contrast to the previous reports. 10,12,13 All eyes treated with Mitomycin C, however, showed no development of a pseudopterygium during the follow-up. Therefore, a beneficial effect of Mitomycin C on postoperative pseudopterygium formation has to be considered likely.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7] The use of amniotic membrane transplantation in the removal of a limbal dermoid has recently been described by others. 10,12,13 The main reasons for using amniotic membrane transplantation on conjunctival defects are the positive effects on reepithelialization and inhibition of postoperative inflammation, neovascularisation, and fibrosis. 17 Pirouzian et al 11 reported that the purpose of amniotic membrane transplantation was primarily to achieve a volumetric filling of the stromal and epithelial defect after the removal of a limbal dermoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many different opinions about the optimal method and appropriate time for removal of these tumors [5]. Obtaining a thorough history, serial monitoring of the dermoid during office visits using cycloplegic retinoscope to measure the dermoid's size, assessment for change in amblyopia, and the use of ultrasound biomicroscopy to assess the involvement of Descemet's membrane play a big role in the choice of what surgical technique to use [9]- [11]. Authors have found optical coherence tomography (OCT) helpful in determining the depth of the dermoid involvement in cornea.…”
Section: Introductionmentioning
confidence: 99%